Demographic history, current expansion and future management challenges of wild boar populations in the Balkans and Europe - Veličković, N; Ferreira, E; Djan, M; Ernst, M; Obreht Vidaković, D; Monaco, A; Fonseca, C (Heredity, 2016)
Wild boar (Sus scrofa), one of the most widespread wildlife species, has entered a stage of continuous growth in Europe, and could even be considered a pest species. We analysed microsatellite variability in 723 wild boars from across Europe, including the northern Dinaric Balkans. Our aims were: (1) to define the population structure of wild boars in the Balkans and its relation with other European populations; (2) to estimate effective populations sizes, levels of intra- and inter-population diversity, inbreeding migration and gene flow patterns; (3) to test subpopulations for bottlenecks; (4) to interpret these results in light of current knowledge about the demographic history of wild boars in Europe; and (5) to discuss the relevance of these findings for management and conservation. Strong population structuring was observed and 14 subpopulations were revealed. High genetic diversity was found, and besides the well-known identity of the Italian populations of Sardinia and Castelporziano, we bring new insights into other potential relevant, refugial populations such as Littoral Slovenia, South Portugal, North-western Iberia and an entire cluster in the Balkans. There was evidence of gene flow going from these refugial subpopulations towards less peripheral and more admixed subpopulations. Recent population bottlenecks and expansions were detected, mostly in the peninsular refuge subpopulations. The results are consistent with the fluctuations of wild boar numbers in Europe since the beginning of the twentieth century. These results should be taken into account in future conservation and management plans for wild boar populations in Europe.
Keywords: tok genů; populační genetika; Sus scrofa; Population Density; Population Dynamics; Genetics, Population; Microsatellite Repeats; Genotyping Techniques; Gene Flow; hustota populace; frekvence genu; genotypizační techniky; inbreeding; zvířata; Europe; Models, Statistical; genetická variace; populační dynamika; Genetic Variation; zachování přírodních zdrojů; modely genetické; Conservation of Natural Resources; Inbreeding; Gene Frequency; mikrosatelitní repetice; statistické modely; Balkánský poloostrov; Models, Genetic; Animals; Balkan Peninsula; Evropa